Removal of Pesticides Using Aquatic Plants in Water Resources: A Review - Chander P.D.; Fai C.M.; Kin C.M. (Institute of Physics Publishing, 2023)
Animals; Bioremediation; Cost effectiveness; Health hazards; Heavy metals; Pesticides; Vegetables; Water pollution; Agriculture applications; Beneficial effects; Economic production; Environment quality; European regulation; Food and agriculture organizations; Inorganic pollutants; Phytoremediation technology; Chemicals removal (water treatment)